IMPLEMENTING ABCD TOOLS AND PROCESSES IN THE CONTEXT OF SOCIAL WORK STUDENT PRACTICE - Mansvelt, Natalie (Social Work/Maatskaplike Werk, 2018)
Social workers tend to be apprehensive about macro-level work and community development, despite community development being a key strategy in developmental social welfare. All student social workers in South Africa are required to develop knowledge, skills and field practice experience in community development. This article explores the application of asset-based community-driven development (ABCD) in the context of field education. The learning diaries of second-year social work students were analysed in order to gain an understanding of students’ views and experiences of ABCD. The findings reveal that students respond positively to ABCD and start to appreciate the value of community development.